Modulating effect of poling on performance of solar cell based on novel narrow bandgap molecular ferroelectric semiconductor hexane-1, 6-diammoniumpentaiodobismuth. (1st November 2022) - Li, Xiaotong; Zou, Xiaoping; Zhang, Chunqian; Cheng, Jin; Li, Guangdong; Wang, Yifei; Wang, Xiaolan; Song, Keke; Ren, Baokai; Li, Junming
Abstract: In ferroelectric-semiconductor solar cells, the depolarization field formed by the ferroelectric material after poling can constitute a synergistic effect with the built-in electric field of the P–N junction, which can enhance the carrier separation and transport, thus improving the photovoltaic performance, attracting extensive research interest. Hexane-1, 6-diammonium pentaiodobismuth (HDA-BiI5 ) is a narrow bandgap molecular ferroelectric, and solar cells based on it with mesopores and conventional structure have been prepared, but no poling modulation of photovoltaic performance has been studied. In this paper, the effects of poling on the performance of HDA-BiI5 based solar cells with conventional structure are characterized for further studies of HDA-BiI5 based solar cells. The performance can be modulated by poling, improved after positive poling and significantly degraded after negative poling, due to another driving force for charge carrier separation, depolarization filed. Highlights: Modulating effect of poling on performance of HDA-BiI5 based solar cells is observed. Positive poling enhances PV performance, whereas negative poling does the opposite. Depolarization field plays an important role in charge carrier separation mechanism.